A critical investigation of the nature and extent of cyberbullying in two post-primary schools in Northern Ireland. (2nd January 2016) - Purdy, Noel; York, Leanne
Abstract: This study aimed to investigate internet usage among post-primary pupils in years 9, 11 and 13 in two contrasting post-primary schools in Northern Ireland, the nature and incidence of cyberbullying among these pupils, and the ways in which their schools are currently addressing the problem. A mixed methodological approach was adopted: a paper questionnaire was completed by pupils in Years 9, 11 and 13 ( n = 425) in the two post-primary schools; focus group interviews were conducted with pupils from each year group ( n = 18); and individual semi-structured interviews were carried out with the pastoral care coordinators (deputy heads with responsibility for pupil wellbeing) of each school ( n = 2). The findings confirm that the post-primary pupils in these two schools own a range of internet-capable media devices and spend considerable time online. The incidence of cyberbullying among these pupils was relatively low, and most often consisted of hurtful or nasty comments sent via texts or posted on social networking sites. The study reveals inconsistencies between the approaches taken by the two schools, but also generally low levels of staff training, little engagement with parents, a lack of pupil confidence in the school's ability to discuss cyberbullying openly, and a worrying absence of any systematic evaluation of the effectiveness of the schools' current strategies for tackling this complex issue.